(untitled) (African Journal of Biomedical Research, 2022)
Preoperative preparation of the patient which focuses on improvement of health status, intra operative asepsis and other advancements in technology have been shown to facilitate outcome of surgical interventions and speed up post-operative wound healing. This study examines patients’ opinion on determinants of post-operative wound healing in a tertiary health facility in Calabar. Descriptive survey design was adopted for the study. Validated structured four sections interview guide with reliability co-efficient of 0.79 was used to obtained information from 322 patients who were purposively selected and voluntarily participated from the 6 surgical wards in the hospital. Data was analysed using simple percentage and hypotheses were tested using chi-square analysis and independent t-test with the aid of statistical package for social science version 21. Results showed that 189 (58.7%) respondents had positive opinion on co-morbidity factors associated with wound healing, while 133 (41.3%) respondent had negative opinion. On local factors 197 (61.2%) had positive opinion, while 125 (38.8%) respondents had negative opinion. On influence of systemic factors, 189 (58.7%) respondents had positive opinion while 133 (41.3%) respondents had negative opinion. There was a positive significant association (P<0.05) between level of education and patients’ opinion on co-morbidities factors associated with post-operative wound healing. There was no significant difference (P>0.05) between gender and systemic factors influencing post- operative wound healing. Based on these findings, it was recommended that Nurses should carry out health talks in clinics on wound hygiene and positive lifestyles for health promotion